Supply Chain Technical Alliances and Performance of Manufacturing Firms in Kenya - Rajab, Fatuma; Ngugi, Patrick; Kiarie, David (International Journal of Supply Chain Management, 2023)
Purpose: The purpose of this study was to examine the effect of supply chain technical alliances on performance of manufacturing firms in Kenya Methodology: The correlational research design was used in carrying out the study. The study used Fisher's formula to sample 234 manufacturing firms from the total population of 596 registered in Kenya Association of Manufacturers directory. The respondents of the study included managers in all 234 selected manufacturing firms. This research utilized a structured questionnaire to collect data. The study used SPSS version 25.0 to code, process and to carry out descriptive and inferential analysis. The analysed data was displayed using tables, graphs, and bar charts. Results: Supply chain technical alliances has positive and significant relationship with performance of manufacturing firms in Kenya at p<0.05. This implies that upholding and enhancing supply chain technical alliances activities leads to improvements in performance of manufacturing firms in Kenya. The regression model established that the R value was 0.651 while the R2 was 0.423 which indicated that the variability of the supply chain technical alliances on the performance of manufacturing firms in Kenya could be explained by up to 63.1% of the model and the P-value was 0.000<0.05. This implies that the model was fit to determine the relationship between supply chain technical alliances and performance of manufacturing firms in Kenya and therein make conclusions and recommendations. Unique Contribution to Theory, Practice and Policy: While the existing Social exchange theory of supply chain technical alliances used in this study was validated, the study recommends that managers in each manufacturing firm need to consider having supply chain technical alliances strategies in place as it leads to high organizational performance. The firms should ensure they collaborate with other firms on technical skills, sharing technology and acquired knowledge. The study recommended that manufacturing firms policy makers need to establish a policy framework to expedite effective strategies for supply chain technical alliances adoption to facilitate performance of their business operations.